Pretreatment method for formation and display of austenite grain size of low-carbon steel
By designing thin sections and performing precise heat treatment on low-carbon steel samples, combined with cooling using an ice-water mixture, the problem of insufficient hardenability in the detection of austenitic grain size in low-carbon steel was solved, achieving complete display of the martensitic structure and improving the accuracy and efficiency of the detection.
Patent Information
- Application Number
- CN202511486563.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-17
- Publication Date
- 2026-01-23
AI Technical Summary
Existing technologies for detecting austenite grain size in low-carbon steel suffer from poor hardenability, resulting in a higher ferrite content in the microstructure. This makes it difficult to effectively display the original austenite grain boundaries, easily leading to false detections and wasting time and costs.
A thin sheet sample with dimensions of 20mm x 20mm x (3mm to 7mm) was designed. Combined with a heat preservation time of 895±5℃ and a strong cooling scheme of edible salt + ice water mixture, the austenite was completely transformed into martensite. After hot embedding and polishing, it was etched with a 4% nitric acid alcohol solution.
It significantly improves the success rate of first-pass etching of austenite grains, ensures the integrity of martensite structure, avoids false detections, and improves detection efficiency and accuracy.
Smart Images

Figure CN121384557A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metallographic testing technology, specifically a pretreatment method for the formation and display of austenite grain size in low-carbon steel. Background Technology
[0002] The austenite grain size of steel has a significant impact on its mechanical properties, processing properties, chemical properties, and heat treatment. Therefore, the assessment of austenite grain size is of great importance for judging the quality of steel and verifying the correctness of hot working processes.
[0003] Currently, for ordinary carbon steel with a carbon content of 0.05% to 0.10%, ferrite grain size is generally tested, and there are few cases in the industry of testing austenite grain size. However, a small number of products still require the use of the direct hardening method to test the austenite grain size of this type of steel. When testing cubic samples with a side length of 20mm using the direct hardening method, due to the low carbon content, the microstructure of the quenched sample often has a high ferrite content, making it impossible to effectively display the original austenite grain boundaries. If the inspectors fail to detect the microstructure abnormality in time and directly use saturated picric acid etching, it is easy to cause false detections, wasting time and costs. Summary of the Invention
[0004] The purpose of this invention is to provide a pretreatment method for the formation and display of austenite grain size in low-carbon steel, so as to solve the problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a pretreatment method for the formation and display of austenite grain size in low-carbon steel, comprising the following steps: Step 1: preparing and sampling a low-carbon steel billet to be inspected, wherein the carbon content of the low-carbon steel is 0.05% to 0.10%; Step 2: subjecting the sample obtained in Step 1 to heat treatment; Step 3: subjecting the heat-treated sample to grinding and polishing treatment; Step 4: subjecting the grinding and polishing treated sample to etching treatment with a 4% nitric acid alcohol solution and examining the microstructure.
[0006] Preferably, the sample prepared in step one is a thin sheet sample with dimensions of 20mm × 20mm × (3mm to 7mm) in length × width × thickness.
[0007] Preferably, in step one, wire cutting, high-speed sawing or metallographic cutting machine is used for sampling to ensure that the surface of the prepared sample is smooth and free of obvious processing marks.
[0008] Preferably, in step two, the heat treatment involves starting the timer and holding the sample at the furnace temperature after it reaches the set temperature, and then water-cooling the sample after the holding period is over.
[0009] Preferably, the heat preservation temperature in step two is 895±5℃, the heat preservation time is 1.5h-2h, after the heat preservation is completed, the sample is taken out of the furnace and water-cooled within 5s, and the clamps do not touch the sample during the sample transfer process. The sample is stirred continuously for at least 1min during the water cooling process.
[0010] Preferably, the cooling water in step two is a mixed solution of edible salt and water, and an appropriate amount of ice is added to the water to make the cooling medium a mixture of ice and water, and the standing time of the ice and water mixture is not less than 30 minutes.
[0011] Preferably, in step three, the heat-treated sample is subjected to heat-mounting treatment before grinding and polishing.
[0012] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0013] This invention addresses the problem of insufficient hardenability in traditional methods, significantly improving the success rate of first-pass etching of austenite grains. Traditional direct hardening methods using 20mm cube samples for testing low-carbon steel suffer from poor hardenability due to low carbon content and large sample size. This results in a large amount of ferrite remaining in the microstructure after quenching, failing to effectively reveal the original austenite grain boundaries. Furthermore, it easily leads to false detections due to the failure to promptly detect microstructural anomalies and direct etching with saturated picric acid. This invention designs the sample as a thin sheet (length × width × thickness 20mm × 20mm × (3mm~7mm)), employs a precise holding temperature of 895±5℃ for 1.5h-2h, and a strong cooling scheme of "table salt + ice water mixture" (water cooling within 5 seconds after removal from the furnace, stirring for at least 1 minute), ensuring that the austenite formed at high temperature can completely transform into martensite. This completely solves the core problem of "inability to obtain complete martensite through hardening," thereby greatly improving the success rate of first-pass etching of austenite grains in low-carbon steel and effectively avoiding the waste of time and costs caused by false detections. Attached Figure Description
[0014] Figure 1 This is a schematic diagram of the microstructure of low-carbon steel obtained by etching according to the original method in Comparative Example 1 after heat treatment.
[0015] Figure 2 This is a schematic diagram of the microstructure of low-carbon steel obtained after heat treatment by etching using the method of Example 2 of the present invention;
[0016] Figure 3 This is a schematic diagram of the microstructure of low-carbon steel obtained after heat treatment following etching using the scheme in Example 3 of the present invention. Detailed Implementation
[0017] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] This invention provides a pretreatment method for the formation and display of austenite grain size in low-carbon steel, comprising the following steps:
[0019] Step 1: Prepare and sample the low-carbon steel billet to be inspected. The sample size is a thin sheet with a length × width × thickness of 20mm × 20mm × (3mm to 7mm). The carbon content of the low-carbon steel is 0.05% to 0.10%. Use wire cutting, high-speed saw or metallographic cutting machine to take the sample to ensure that the surface of the prepared sample is smooth and without obvious processing marks.
[0020] Step 2: Heat-treat the sample obtained in Step 1; the heat treatment involves starting the timer after the sample is placed in the furnace at the desired temperature, and then water-cooling the sample after the heat treatment is completed. The heat treatment temperature is 895±5℃ and the heat treatment time is 1.5h-2h. After the heat treatment is completed, the sample is removed from the furnace and water-cooled within 5s. During the sample transfer process, the clamps should not touch the sample. The sample should be stirred continuously for at least 1 minute during the water cooling process. The cooling water is a mixed solution of edible salt and water, and an appropriate amount of ice is added to the water to make the cooling medium an ice-water mixture. The ice-water mixture should be left to stand for at least 30 minutes.
[0021] Step 3: Perform heat mounting on the heat-treated sample, followed by polishing.
[0022] Step 4: After polishing, the sample is etched with a 4% nitric acid alcohol solution and the microstructure is examined.
[0023] The following is an illustrative description of the pretreatment method for the formation and display of austenite grain size in low-carbon steel. It should be noted that this example is merely a specific embodiment of the present invention and does not limit the scope of protection of the present invention.
[0024] Comparative Example 1 (Traditional direct hardening method, control group)
[0025] This embodiment employs traditional industry testing processes to highlight the shortcomings of existing technologies. The specific steps are as follows:
[0026] Sample Preparation: The low-carbon steel billet to be tested was prepared using a band saw, resulting in a cube with a side length of 20 mm (consistent with the traditional sample size mentioned in the background section). Due to the limited precision of the band saw, obvious machining marks were present on the surface of the prepared sample. Because of these marks, the sample before heat treatment required multiple rounds of rough and fine grinding, followed by polishing to remove surface defects and obtain a smooth surface.
[0027] Sample heat treatment: The cubic samples were placed in a heating furnace and the heat treatment process was 890℃ for 1 hour followed by conventional water cooling. However, the heating furnace did not strictly adhere to the "entering the furnace at the designated temperature" timing, and the holding time was only 1 hour. During the water cooling process, the cooling medium was not specially treated (it was room temperature tap water), and the transfer time from the sample exiting the furnace to entering the water exceeded 5 seconds. The sample was not continuously stirred during water cooling.
[0028] Corrosion and Microstructure Examination: The polished samples were corroded using a 4% nitric acid-alcohol solution. After corrosion, the microstructure was observed under a microscope. The results are as follows: Figure 1 As shown.
[0029] Depend on Figure 1 It can be seen that the microstructure obtained in this embodiment contains a large amount of equiaxed ferrite, and the matrix martensite structure is incomplete. This is because the traditional cubic sample has poor hardenability, insufficient holding time and insufficient cooling intensity, which causes the austenite formed at high temperature to fail to completely transform into martensite. The residual ferrite covers the original austenite grain boundaries and cannot meet the requirements of subsequent austenite grain size detection. This is completely consistent with the problem in the background art that "traditional methods cannot effectively display the original austenite grain boundaries".
[0030] Example 1 (Method of the present invention, Experimental Group 1)
[0031] This embodiment uses the preprocessing method proposed in this invention, and the specific steps are as follows:
[0032] Sample Preparation and Sampling: The low-carbon steel blank to be tested was prepared using a metallographic cutting machine. Strict control of processing precision was maintained, resulting in a thin sheet with dimensions of length × width × thickness = 20mm × 20mm × 5mm. The prepared sample had a smooth surface without obvious processing marks, eliminating the need for additional grinding and polishing before heat treatment.
[0033] Sample heat treatment:
[0034] Heating control: Place the thin sheet sample into the heating furnace. After the furnace temperature rises to 900℃ (within the process range of 895±5℃) and stabilizes, place the sample into the furnace and start timing the heat preservation. The heat preservation time is 1.5h (meeting the heat preservation requirements of 1.5h to 2h) to ensure that the carbon content in the austenitic structure is uniform and to avoid surface oxidation and decarburization.
[0035] Cooling control: After the heat preservation is completed, the sample is quickly removed from the furnace within 5 seconds. During the transfer process, a special clamp is used to ensure that the clamp does not touch the sample. The cooling medium is a mixed solution of edible salt and water (with an appropriate amount of ice added, let stand for more than 30 minutes to form an ice-water mixture). After the sample is placed in the cooling medium, the sample is continuously stirred for more than 1 minute to ensure that the sample is fully cooled. Trays and other containers are not placed in the cooling medium together to avoid a rapid rise in water temperature.
[0036] Sample polishing treatment: First, the heat-treated thin sheet sample is heat-mounted (meeting the requirements of step three of this invention, "heat mounting before polishing"), so that the sample is wrapped with thermosetting resin (phenolic resin) to form a regular mounting block; then the mounting block is subjected to coarse grinding, fine grinding and polishing treatment in sequence. Because the sample is fixed by the resin, there is no deformation or warping during the polishing process, and a flat test surface is finally obtained, while effectively preserving the "corrosion-prone area" on the outer surface of the sample.
[0037] Corrosion and Microstructure Examination: The polished mounting samples were etched using a 4% nitric acid alcohol solution (prepared and etched according to relevant standards). After etching, the microstructure was observed under a microscope. The results are as follows: Figure 2 As shown.
[0038] Depend on Figure 2 As can be seen, the microstructure obtained in this embodiment has no ferrite structure and the matrix martensite structure is complete. This is because the thin sheet sample improves hardenability, the precise heat preservation parameters ensure the homogenization of austenite, and the cooling intensity of the ice-water mixture ensures that austenite is completely transformed into martensite. The complete martensite structure can clearly reflect the original austenite grain boundaries, providing a good microstructure basis for subsequent austenite grain size detection.
[0039] Example 2 (Method of the present invention, Experimental Group 2)
[0040] To further verify the stability and applicability of the method of the present invention, this embodiment adjusts the sample thickness and heat treatment parameters. The specific steps are as follows:
[0041] Sample preparation and sampling: The low carbon steel blank to be tested (the same batch of material as in Example 2) was sampled and prepared using a metallographic cutting machine. The final sample size was a thin sheet with a length × width × thickness of 20 mm × 20 mm × 6 mm (still within the thin sheet size range of 3 mm to 7 mm). After preparation, the sample surface was smooth and without knife marks.
[0042] Sample heat treatment:
[0043] Heating control: Place the thin-film sample into the heating furnace. After the furnace temperature rises to 895℃ (the center value of 895±5℃) and stabilizes, place the sample in the furnace and start timing the heat preservation. The heat preservation time is 1.6h (within the range of 1.5h to 2h).
[0044] Cooling control: After the heat preservation is completed, the sample is quickly removed from the furnace within 5 seconds. The clamps do not touch the sample during the transfer. The cooling medium is the same as in Example 2, which is a mixture of "edible salt and ice water". After the sample is put into the water, it is stirred continuously for more than 1 minute to ensure sufficient cooling.
[0045] Sample polishing: Similar to Example 2, the heat-treated sample is first heat-mounted and then polished to obtain a smooth test surface.
[0046] Corrosion and Microstructure Examination: Corrosion was performed using a 4% nitric acid-alcohol solution. The microstructure was then observed, and the results are as follows: Figure 3 As shown.
[0047] Depend on Figure 3 As can be seen, the microstructure obtained in this embodiment is consistent with that in Example 2, with no ferrite residue and a complete martensite matrix. This indicates that the method of the present invention can stably achieve the effect of "complete transformation of austenite into martensite" within a reasonable range of sheet size (3mm to 7mm) and heat treatment parameters (890℃ to 900℃, 1.5h to 2h), further verifying the reliability of the method of the present invention, which is not affected by small-range parameter adjustments.
[0048] In summary, a comparison of Comparative Example 1 (traditional method) with Examples 1 and 2 (the method of this invention) shows that the traditional method, due to defects in sample size (cubic) and heat treatment parameters (short holding time and insufficient cooling intensity), results in incomplete martensite structure and cannot meet the detection requirements.
[0049] This invention, through a combination of "thin-sheet sample design + precise heat treatment process + ice water cooling + hot inlay grinding and polishing", can stably obtain a complete martensitic structure, effectively solving the core problem of "inability to display the original austenite grain boundaries" in the direct hardening method of low carbon steel, and providing a key guarantee for the accurate detection of subsequent austenite grain size.
[0050] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A pretreatment method for the formation and display of austenite grain size in low-carbon steel, characterized in that: Including the following Steps: Step 1: Prepare and sample the low-carbon steel billet to be inspected. The carbon content of the low-carbon steel is 0.05% to 0.10%. Step 2: Heat-treat the sample obtained in Step 1. Step 3: Grind and polish the heat-treated sample. Step 4: Etch the polished sample with a 4% nitric acid alcohol solution and examine the microstructure.
2. The pretreatment method for the formation and display of austenite grain size in low-carbon steel according to claim 1, characterized in that: After step one, the sample is a thin sheet with dimensions of 20mm x 20mm x (3mm to 7mm) in length x width x thickness.
3. The pretreatment method for the formation and display of austenite grain size in low-carbon steel according to claim 1, characterized in that: Step one involves taking samples using wire cutting, high-speed sawing, or metallographic cutting to ensure that the prepared sample surface is smooth and free of obvious machining marks.
4. The pretreatment method for the formation and display of austenite grain size in low-carbon steel according to claim 1, characterized in that: The heat treatment in step two involves starting the timer and holding the sample at the furnace temperature after it reaches the set temperature. After the holding period, the sample is cooled with water.
5. The pretreatment method for the formation and display of austenite grain size in low-carbon steel according to claim 1, characterized in that: The holding temperature in step two is 895±5℃, and the holding time is 1.5h-2h. After the holding time is completed, the sample is removed from the furnace and cooled in water within 5s. During the sample transfer process, the clamps should not touch the sample. The sample should be stirred continuously for at least 1 minute during the water cooling process.
6. The pretreatment method for the formation and display of austenite grain size in low-carbon steel according to claim 1, characterized in that: The cooling water in step two is a mixed solution of edible salt and water, with an appropriate amount of ice added to make the cooling medium a mixture of ice and water. The ice-water mixture should be left to stand for at least 30 minutes.
7. The pretreatment method for the formation and display of austenite grain size in low-carbon steel according to claim 1, characterized in that: Step 3 involves heat-mounting the heat-treated sample before grinding and polishing.